2000
DOI: 10.1128/mcb.20.11.4169-4180.2000
|View full text |Cite
|
Sign up to set email alerts
|

S-Phase Progression Mediates Activation of a Silenced Gene in Synthetic Nuclei

Abstract: Aberrant expression of developmentally silenced genes, characteristic of tumor cells and regenerating tissue, is highly correlated with increased cell proliferation. By modeling this process in vitro in synthetic nuclei, we find that DNA replication leads to deregulation of established developmental expression patterns. Chromatin assembly in the presence of adult mouse liver nuclear extract mediates developmental stage-specific silencing of the tumor marker gene alpha-fetoprotein (AFP). Replication of silenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Postnatal AFP repression in liver is coincident with the cessation of hepatocyte cell division, and AFP reactivation is often related to the hepatocyte proliferation (e.g., regeneration and carcinogenesis) (1). It is thought that there may be a mechanistic link behind this temporal correlation, which is further supported by in vitro studies of AFP reactivation (30). However, the adult LZB20KO liver has a normal architecture and remains in a normally nonproliferating status, despite their aberrant expression of AFP.…”
Section: Discussionmentioning
confidence: 89%
“…Postnatal AFP repression in liver is coincident with the cessation of hepatocyte cell division, and AFP reactivation is often related to the hepatocyte proliferation (e.g., regeneration and carcinogenesis) (1). It is thought that there may be a mechanistic link behind this temporal correlation, which is further supported by in vitro studies of AFP reactivation (30). However, the adult LZB20KO liver has a normal architecture and remains in a normally nonproliferating status, despite their aberrant expression of AFP.…”
Section: Discussionmentioning
confidence: 89%
“…We performed ChIP analyses of developmentally staged mouse liver tissue to determine relative levels of endogenous p53, LSD1, and H3K4me2 present at the developmental repressor region (SBE/p53RE) (60) of AFP chromatin. Our previous work showed that this intercalated Smad/p53 response element is essential for p53-mediated repression of AFP in cultured cells and by in vitro transcription (11,34). Shortly after birth, when hepatic AFP expression is robust (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…At low expression tetO promoters exhibit transcriptional pulses that originate around the G1 to S transition when DNA replication occurs. S phase progression has been suggested to affect transcription [47] and has been established as important to (de)silence gene loci in a manner that either requires replication fork progression [48], [49] or not [50], [51]. Replication-dependent transcriptional activation of viral genes has been reported in transient transfection assays, and depends on trans activators that bind to either the proximal promoter or and enhancer region [52], [53].…”
Section: Discussionmentioning
confidence: 99%